SINKRONISASI REGULASI PEMBAYARAN TUNAI DAN NON-TUNAI: ANTARA INOVASI DIGITAL DAN KEPATUHAN PADA UU MATA UANG - Tombi, Johan Tri Noval Hendrian; I Kadek Sudiarsana; Gegana, Reza Pramasta; Luthfan, Gusti Fadhil Fithrian; Fajrin, Fera Wulandari; Raden, Andi Nur Fikriana Aulia (JUSTITIABLE - Jurnal Hukum, 2026)
This study aims to analyze the regulatory synchronization between innovations in digital payment systems and the obligation to use physical currency (cash) as a lawful means of payment. The principal issue examined is the growing prevalence of exclusive cashless policies adopted by business actors, which, in legal terms, result in the refusal to accept cash rupiah. The research employs a normative juridical method, using a statutory approach and a comparative approach. The findings indicate that the unilateral refusal to accept cash constitutes a violation of mandatory legal norms, rendering such agreements null and void by operation of law. From a sociological perspective, these policies create barriers to economic access for unbanked populations as well as for elderly groups. The study concludes that a policy reorientation is necessary to ensure the implementation of the mandate of Article 23 of the Currency Law. Accordingly, this research recommends the application of graduated administrative sanctions, ranging from financial penalties to the suspension of QRIS services, in order to ensure inclusivity and legal certainty within the national payment system.